Fortifying the future: A comprehensive study of fin-tech security measures - Temani, Vishnu Priya (Indian Journal of Public Administration)
This article provides a comprehensive study of security measures in the financial technology (fin-tech) sector, focusing on the challenges and innovations shaping digital finance. It examines the vulnerabilities inherent in fintech platforms, including risks related to data breaches, fraud, and regulatory compliance. The study highlights key security measures such as encryption, multi-factor authentication, risk management frameworks, and advanced monitoring systems designed to safeguard financial transactions and user data. By situating fintech security within the broader context of digital infrastructure and financial innovation, the paper underscores the importance of robust security protocols in fortifying the future of digital finance and ensuring trust in rapidly evolving financial ecosystems.
Keywords: Technology, Fin-Tech, Cyber Security, Digital Finance, Security Measures, Data Protection, Financial Technology, Risk Management, Encryption, Fraud Prevention, Regulatory Compliance, Digital Infrastructure